Ultra sensitive microfluidic immunosensor for determination of clenbuterol in bovine hair samples using electrodeposited gold nanoparticles and magnetic micro particles as bio-affinity platform - Regiart, Daniel Matias Gaston (2013)
In this article, we report the first integrated microfluidic immunosensor coupled to a screen-printed carbon electrode (SPCE) applied to determination of clenbuterol (CLB) in bovine hair samples. CLB is a member of the β2-agonist drugs which is used in animal production and is banned in Argentine and the European Union. It represents a potential risk and has to be carefully monitored to avoid the illegal use of high amounts of this compound that could result in human food poisoning. In order to perform the CLB detection, the SPCE was modified by gold nanoparticles (AuNPs) electrodeposition. Quantitative determination of CLB was carried out using a competitive indirect immunoassay, method based on the use of anti-CLB antibodies immobilized on magnetic micro particles. The CLB present in bovine hair samples competes immunologically with alkaline phosphatase (AP) enzyme-labeled CLB conjugate for the anti-CLB specific antibodies. Later, p-aminophenyl phosphate was converted to p-aminophenol by AP, and the electroactive product was quantified on AuNPs/SPCE at +0.1 V. The limit of detection for electrochemical method was 0.008 ng mL−1 and the intra- and inter-assay coefficients of variation were below 6%. This being a veterinary control tool very useful for rapid, sensitive and selective detection of CLB in an “in vitro” technique.